Penerapan SIPD RI di Bappelitbangda Kota Bekasi Berdasarkan Perspektif HOT-FIT Framewok - Zahra Amelia; Dewi Noor Azijah; Lolita Deby Mahendra (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This study aims to analyze the implementation of the Indonesian Regional Government Information System (SIPD RI) in the Bekasi City Development Planning Agency (Bappelitbangda) based on the HOT-Fit framework developed by Yusof et al. (2008). This study uses a descriptive case study method with a qualitative approach. Primary data was obtained through in-depth interviews, observations, and documentation. Secondary data was sourced from regulations, literature, and official documents of the Bekasi City Bappelitbangda. Data analysis was conducted through the stages of reduction, presentation, and conclusion drawing based on the three main dimensions of HOT-Fit.The results of the study show that in terms of human resources, the use of SIPD RI has become a tool in daily work, one of which is in regional financial management, but there are still competency gaps that require ongoing training and technical assistance. In the organizational dimension, policy support and commitment from local leaders are clear, but internal technical support remains limited. In the technological dimension, SIPD RI excels in data entry efficiency, ease of access, and data format consistency, but is hindered by network disruptions, a validation process that involves several stages, lack of integration with other systems, and limited reporting features. This study concludes that the implementation of SIPD RI at Bappelitbangda of Bekasi City has been carried out in accordance with regulations and supports transparency and accountability in local financial management. However, optimization in the areas of human resources, organizational coordination, and system development is still needed to enhance the effectiveness and quality of local financial management